1995
DOI: 10.1172/jci118217
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and insulin-like growth factor-I enhance human skeletal muscle protein anabolism during hyperaminoacidemia by different mechanisms.

Abstract: Insulin inhibits proteolysis in human muscle thereby increasing protein anabolism. In contrast, IGF-I promotes muscle protein anabolism principally by stimulating protein synthesis. As increases or decreases of plasma amino acids may affect protein turnover in muscle and also alter the muscle's response to insulin and/or IGF-I, this study was designed to examine the effects of insulin and IGF-I on human muscle protein turnover during hyperaminoacidemia. We measured phenylalanine balance and [3HI -phenylalanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(146 citation statements)
references
References 48 publications
(47 reference statements)
6
137
2
1
Order By: Relevance
“…Insulin had no effect on MPS when AA delivery was unchanged from baseline. These results are also supported by other studies [17, 20, Louard et al(a) 1992 [19] Fryburg et al 1995 [26] Timmerman et al (1b) 28-31, 34, 44]. In all healthy human studies where AA availability has been reduced, MPS has been reduced or remained unchanged [18,19,37,45,46], even in the presence of supraphysiological concentrations of insulin [18].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Insulin had no effect on MPS when AA delivery was unchanged from baseline. These results are also supported by other studies [17, 20, Louard et al(a) 1992 [19] Fryburg et al 1995 [26] Timmerman et al (1b) 28-31, 34, 44]. In all healthy human studies where AA availability has been reduced, MPS has been reduced or remained unchanged [18,19,37,45,46], even in the presence of supraphysiological concentrations of insulin [18].…”
Section: Discussionsupporting
confidence: 78%
“…Meta-analysis of study characteristics A total of 13 articles [16,[19][20][21][24][25][26][27][28][29][30][31][32], containing 25 experimental studies using different insulin concentrations, were identified for inclusion in the meta-analysis (Table 1); all analysed the effect of insulin on both MPS and MPB (Table 1). A total of 173 individuals were included in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…IGF-I has strong insulin-like metabolic effects (13). In particular, IGF-I stimulates protein synthesis (38) and inhibits protein breakdown (39); it is an anabolic hormone. Plasma IGF-I levels are regulated by nutrition, via plasma insulin levels and protein and calorie intake (12).…”
Section: Discussionmentioning
confidence: 99%
“…24 Obese animals, both diet induced and genetically, are hyperinsulinaemic. 25±27 In the diet-obese group, the increase in amino acid availability, due to increased arterial blood concentrations and the increased blood ow, could generate a favourable gradient that facilitates muscle uptake of many amino acids, 28 mainly Ala, Val and Arg (the relative extraction ratio for these amino acids were: 8, 24 and 24% respectively). The uptake of Ala could be favoured by the insulin induction of the transport system A 24 although this pattern may not be followed by other amino acid transport systems, since the uptake relates amino acid availability with a dubious activation of other selective transport systems.…”
Section: Discussionmentioning
confidence: 99%